Sikke et ord - Thrane, Torben (HERMES - Journal of Language and Communication in Business, 2001)
There is an apparently peripheral construction type that falls outside the normally mandatory V2-structure of Danish main clauses, expressions introduced by the emphatic lexical item sikke (plus inflectional variants sikken, sikket). Such expressions defy standard taxonomic descriptions of Danish and pose a challenge to current formal (GB/PP/Minimalist) generalizations about movement operations. This paper aims to give not only a coherent description of such expressions in morphological, syntactic, and semantic terms, but also proposes a simple mechanism for information-sharing between nodes in addition to overt and - especially - covert movement. Given this mechanism it is shown that the description of a number of other and seemingly disparate aspects of Danish syntax follows naturally from the assumption that they are all instantiations of ’breakstructure’.